Case report: Acute Hepatitis E Infection with Co-Existent Glucose-6-Phosphate Dehydrogenase Deficiency - Amitabh Monga; Ravinder PS Makkar; Anju Arora; Surabhi Mukhopadhyay; Ajay K Gupta (Canadian Journal of Infectious Diseases)
Hepatitis E virus is one of the leading causes of acute viral hepatitis in India but usually manifests as a mild self-limiting illness. Viral hepatitis in the presence of glucose-6-phosphate dehydrogenase (G6PD) deficiency may be associated with complications such as severe anemia, hemolysis, renal failure, hepatic encephalopathy and even death. The incidence of G6PD deficiency in the general population of northern India is reported to be between 2.2% and 14%. Despite both hepatitis E infection and G6PD deficiency being common, their impact on patient illness has only recently been reported. The present study reports a case of severe hemolysis in a patient with G6PD deficiency and hepatitis E infection.